ANALYSIS OF SELECTED SOLUTIONS AND METHODS TO LIMIT THE UNEVEN LOAD DISTRIBUTION ON THE TOOTH WIDTH - Michał JUZEK; Grzegorz WOJNAR (Scientific Journal of Silesian University of Technology. Series Transport, 2017)
This article is dedicated to the subject of gearboxes, with a specific focus on the load distribution on the tooth. The aim of the study was to review the selected solutions and methods that can contribute to aligning the load on the width of the tooth. The structure and operation of each solution are described in detail. The paper presents the possible benefits of using the described solutions.